Распространение, численность и вертикалыю-биотопическое распределение сов Копетдага в пределах СССР - Мищенко, Ю.В. (Вестник зоологии, 1982)
The data o n occurrence and ecologyo fOtus scops (L.), O. brucei.(Hume),Bubo bubo L., Athene noctua_ (Scop.) and Strix aluco L. The nesting of Asio otus L. for the first time is shown for Kopet-Dagh mountains. Habitat and vertical distribution si descri- bed in detail, the causes of limited occurrence o most owl species within studied area are discussed.